CULTURAL INTELLIGENCE AND RESISTANCE TO REVERSE CULTURE SHOCK : THE CASE OF INTERNATIONAL STUDENTS INTERNSHIP IN JAPAN: KECERDASAN BUDAYA DAN KETAHANAN BUDAYA LOKAL: STUDI KASUS CULTURAL INTELLIGENCE DAN REVERSE CULTURE SHOCK MAHASISWA MAGANG DI JEPANG - Oslan Amril; Elfiondri Elfiondri; Irma Irma; Diana Kartika (Jurnal Kata, 2022)
Literature study shows that International students experience culture shock both to foreign cultures and to their own local cultures (reverse culture shock). Unfortunately, the study on resistance to reverse culture shock is rather neglected. This paper examines the students’ reverse culture shock in relation to cultural intelligence, the case of international students internship in Japan. The aim is to find out cultural intelligence, resistance to reverse culture shock, and the influence of cultural intelligence on resistance to reverse culture shock. The study uses quantitative methods with SEM-PLS statistical tests, and theoretical approaches to culture shock, reverse culture shock, and cultural intelligence. The results of the study are that international students participating in internships in Japan do not experience culture shock to Indonesian culture as a local culture. Generally, they have a good resistance to the reverse culture shock of their local culture. They do not feel a shock to Indonesian cultures as their local culture after coming back from Japan. They can resist to the reverse culture shock because they have a good cultural intelligence.  Cultural intelligence has a positive influence on the shock to local Indonesian culture. However, not all of them do not have cultural resistance with a 100% intelligence level. A small number experienced local culture shock (reverse culture shock), meaning that a small number of International students experience a slight shock to Indonesian culture.